1968
DOI: 10.1088/0022-3727/1/5/303
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbon fibre reinforcement on the friction and wear of polymers

Abstract: Thermosetting and thermoplastic polymers have been reinforced with carbon fibres of high strength and elastic modulus, and their friction and wear properties examined. During dry sliding against steel, randomly oriented chopped fibres reduce both the coefficients of friction and the wear rates of polymers to levels which are approximately independent of the matrix material. Fibre orientation is also important, and minimum wear is obtained when the fibres are normal to the sliding surface. Carbon fibre reinforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(94 citation statements)
references
References 2 publications
5
89
0
Order By: Relevance
“…The differences between the GF-and CF-based samples regarding the friction-coefficient values are due to different tribological characteristics of the two fiber types, where the carbon fiber is an anti-friction material 37 , while the glass fiber promotes friction. 38 …”
Section: Tribological Testingmentioning
confidence: 99%
“…The differences between the GF-and CF-based samples regarding the friction-coefficient values are due to different tribological characteristics of the two fiber types, where the carbon fiber is an anti-friction material 37 , while the glass fiber promotes friction. 38 …”
Section: Tribological Testingmentioning
confidence: 99%
“…One of the traditional concepts to improve the friction and wear behaviour of polymeric materials is to enhance their hardness, stiffness and their compressive strength and to reduce adhesion to the counterpart material [6][7][8][9]. Many investigations have shown that the incorporation of fiber reinforcement improved the wear resistance and reduced the coefficient of friction [10]. Mody et al [11] in their investigation showed the simultaneous existence of parallel and perpendicular oriented carbon fibers in a woven configuration leads to a synergic effect on the enhancement of the wear resistance of composite.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber is one of the conventional filler materials to improve the mechanical strength and wear resistance of PTFE 1) . Lancaster 1) studied the mechanism of wear reduction in polymers for carbon fiber reinforcement and proposed two factors.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber is one of the conventional filler materials to improve the mechanical strength and wear resistance of PTFE 1) . Lancaster 1) studied the mechanism of wear reduction in polymers for carbon fiber reinforcement and proposed two factors. Firstly, the fibers were exposed at the sliding surface and supported part of the applied load; secondly, the fibers smoothed the surface of the counter face and thus reduced the localized stresses at the asperity contact.…”
Section: Introductionmentioning
confidence: 99%